Предмет: Химия,
автор: жадудеьаььа
Помогите, пожалуйста
Приложения:
Ответы
Автор ответа:
0
2)б)
(Ba^2+) + (2OH^-) + (2H^+) + (2NO3^-) = Ba(NO3)2 + 2H2O -полное ионное
(Ba^2-) + (2NO3^-) = Ba(NO3)2 осадок -сокращенное ионное
4)CaI + H3PO4 = Ca3(PO4)2 осадок + HI
(Ba^2+) + (2OH^-) + (2H^+) + (2NO3^-) = Ba(NO3)2 + 2H2O -полное ионное
(Ba^2-) + (2NO3^-) = Ba(NO3)2 осадок -сокращенное ионное
4)CaI + H3PO4 = Ca3(PO4)2 осадок + HI
Приложения:
Похожие вопросы
Предмет: Геометрия,
автор: al71258303
Предмет: Математика,
автор: daryaprokudina00
Предмет: Математика,
автор: alalalalalla
Предмет: Химия,
автор: Аноним
Предмет: Физика,
автор: kpucmywozka